Customer Perception towards Mobile Wallet - Ahuja, Anjali; Joshi, Richa (IJRDO - Journal of Business Management, 2018)
In present world mobile play an important role in our daily life. A mobile wallet is a way to carry your cards information in a digital form on your mobile device. By using this platform you can make payments for your purchases through Smartphone, tablet or smart watch instead of using card physically. It is a form of e-commerce model that is designed to be used with mobile devices due to their convenience and easy access. In India, the growing adoption of Smartphone’s and mobile phone has given a boost to the mobile wallet industry in India. Players like Pay tm, Mobikwik, free recharge, oxygen etc. have taken charge towards the payment system. The study aims to know the customer perception towards M wallets. Factor analysis technique is used to identify factors which affect customer perception towards M wallets.Keywords: E-commerce, M-wallet, Perception.